Keterlibatan Orang Tua Terhadap Disiplin Belajar Siswa Dalam Mengerjakan Tugas Di Rumah Selama Pandemi - Raden Siti Mariam; Teguh Prasetyo; Abdul Kholik (Jurnal Penjaminan Mutu, 2023)
The involvement of parents in this study includes establishing good family conditions and growing children's intelligence that can support student learning discipline when doing assignments at home during online learning during the COVID-19 pandemic. This study aims to determine whether parental involvement affects student learning discipline in doing chores at home during the pandemic at SDN Sindangsari 2 Bogor City. This study uses a quantitative method with the type of causality correlation research. The sample in this study used the Slovin formula, and the model obtained was 115. The sampling technique used in determining the selection was stratified random sampling, considering the considerations of elements or categories in the research population. This study uses a questionnaire as an instrument in data collection. Data analysis in this study used the SPSS version 25 program. The results of this study indicate that there is a significant influence between parental involvement on student learning discipline in doing assignments at home during the pandemic at SDN Sindangsari 2 Bogor City with the linear regression equation Y = 32.815 + 0.465x and a significance test of 0.000 <0.05 with a t-count value = 6.326 > 1.981 = t table. The magnitude of the influence of parental involvement on student learning discipline in doing assignments at home is obtained from the calculation of the coefficient of determination (r2), which is 26.2%. At the same time, 73.8% were influenced by other factors not examined in this study.